Braided organizations : designing augmented human-centric processes to enhance performance and innovation - Zarka, Michel; Kochanovskaya, Elena; Pasmore, William A. (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
New digital technologies are changing the way organizations are designed and work is done. Companies that have seized this opportunity are finding that they can speed up innovation, enhance collaboration across boundaries, and enable greater commitment and creativity. This totally new approach for digitally-enabled collaboration doesn't stop at the edge of an organization's boundary but extends beyond it in space and time. We refer to these new ways of organizing as "braids" - an intertwined network of contributors with different capabilities, not controlled or managed by a formal hierarchy, who work together to invent ways to accomplish a common purpose in line with organization's mission and strategy. Braids allow significant advantages over traditional, hierarchical, mechanistic and bounded ways of organizing. These include access to knowledge and capabilities that are key to achieving breakthrough levels of performance; improved coordination among individuals and groups performing interdependent tasks; increased organizational agility; enhanced knowledge-processing as experts contribute more directly to the most important technical and strategic decisions; and greater motivation, as people team together to leverage their capabilities to innovate and accelerate performance. Learning from the trailblazing experimentation of companies like Airbus, Procter & Gamble, Red Hat, and Dassault Systemes, this book outlines how to approach designing braided organizations for a variety of purposes, such as enhancing open innovation or enabling greater supply chain adaptability in order to respond to changing customer demands. In the past, human limitations have restricted the ways we organize companies for growth. Today, there's no excuse for allowing the organizational chart as it's currently drawn to constrain possibilities for improved performance and innovation.